2016
DOI: 10.1016/j.vaccine.2016.10.003
|View full text |Cite
|
Sign up to set email alerts
|

The Roma vaccination gap: Evidence from twelve countries in Central and South-East Europe

Abstract: Our findings point out a large difference in vaccination coverage between Roma and non-Roma and support the need for better understanding of factors influencing vaccination among Roma as well as policies that might improve services for Roma in Central and South-East Europe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 19 publications
2
21
0
Order By: Relevance
“…Nevertheless, international evidence generally points to Roma being subject to greater vulnerability for social exclusion, unemployment, poverty and a low educational level that continue to hinder their access to the social determinants of health [2,5,6,20] despite political commitment to address the problem. In its intersection with ethnicity, gender, age and migration status, limited access to the social determinants of health works to produce a gradient of vulnerability in which women, children and foreign Roma are at greater disadvantage [3,7,[23][24][25].…”
Section: Roma Health In Spainmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, international evidence generally points to Roma being subject to greater vulnerability for social exclusion, unemployment, poverty and a low educational level that continue to hinder their access to the social determinants of health [2,5,6,20] despite political commitment to address the problem. In its intersection with ethnicity, gender, age and migration status, limited access to the social determinants of health works to produce a gradient of vulnerability in which women, children and foreign Roma are at greater disadvantage [3,7,[23][24][25].…”
Section: Roma Health In Spainmentioning
confidence: 99%
“…The Roma have considerably poorer health outcomes when compared to non-Roma populations across Europe [1,2]. Studies point to a persistent health gap with Roma experiencing lower vaccination coverage, higher levels of communicable and noncommunicable diseases, higher unmet health needs and higher infant mortality rates, while acknowledging definitional and methodological challenges that limit data comparibility and impact the depth of the evidence base [1,[3][4][5][6][7][8]. In 2005, twelve European countries joined efforts to promote Roma health equity through the Decade of Roma Inclusiona political commitment to tackle the root causes of poor Roma health by enabling the participation of Roma representatives in health governance [9].…”
Section: Introductionmentioning
confidence: 99%
“…Scientifically, higher health-endangering exposures among CEE Roma have been corroborated most rigorously, first by comparative studies on material conditions and lifestyle-related exposures in children (Cook et al 2013;Orton et al 2017) and lately also by studies on healthcare access and quality (e.g. Andreassen et al 2018;Arora et al 2016;Duval et al 2016;Földes et al 2012a;McFadden et al 2018;Sándor et al 2018;Stojanovski et al 2017;Tambor et al 2014). Overall, studies focusing on material circumstances and health-related behaviours in Roma adults, including aspects of sexual and reproductive health, support this picture.…”
Section: Figure 12 Health Indicators For Roma and The General Populamentioning
confidence: 99%
“…The poor health status of CEE Roma is co-maintained by poorer care and access to care, but little is known about what drives and supports these care inequalities. In general, poorer health care for Roma, both in terms of access to and quality of services, has been shown to be common across the region (Arora et al 2016;Duval et al 2016;Földes et al 2012a;Kühlbrandt et al 2014). However, differences in socioeconomic and other circumstances related to standard health care access between patients mostly fail to explain all of these care inequalities (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…However, numerous studies across Europe have found vaccination uptake to be lower amongst Roma compared to non-Roma communities across Europe [21][22][23]. Vaccination uptake has also been reported as lower in Romania compared to other European countries but has not been examined amongst Romanian communities in the UK.…”
Section: Several Of the 2017-18 Measles Outbreaks In England Specificmentioning
confidence: 99%